2016
DOI: 10.5414/cn108835
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset adverse events after a single dose of rituximab in children with complicated steroid-dependent nephrotic syndrome

Abstract: Although neutropenia and hypogammaglobulinemia should be kept in mind as late-onset adverse events of RTX therapy in patients with complicated SDNS, severe infections during B-cell depletion periods are infrequent when our treatment strategies are implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…43,74,85 A condition that has become more frequent in recent years is hypogammaglobulinemia associated with the use of rituximab, an anti-CD20 monoclonal antibody indicated for some autoimmune diseases, lymphoproliferative syndromes, or refractory nephrotic syndrome. This type of hypogammaglobulinemia affects up to 50% of patients, especially those on regular use of rituximab; is symptomatic in less than 10% of cases, and can persist for a long time 86-89 requiring Ig replacement, either intravenous or subcutaneous. 90 Persistent hypogammaglobulinemia may occur in a small group of genetically predisposed patients on rituximab.…”
Section: Indications and Efficacy Of Human Immunoglobulin In Primary mentioning
confidence: 99%
“…43,74,85 A condition that has become more frequent in recent years is hypogammaglobulinemia associated with the use of rituximab, an anti-CD20 monoclonal antibody indicated for some autoimmune diseases, lymphoproliferative syndromes, or refractory nephrotic syndrome. This type of hypogammaglobulinemia affects up to 50% of patients, especially those on regular use of rituximab; is symptomatic in less than 10% of cases, and can persist for a long time 86-89 requiring Ig replacement, either intravenous or subcutaneous. 90 Persistent hypogammaglobulinemia may occur in a small group of genetically predisposed patients on rituximab.…”
Section: Indications and Efficacy Of Human Immunoglobulin In Primary mentioning
confidence: 99%
“…Regarding the risk of severe infections following RTX infusion in paediatric patients affected by NS, among the 27 patients showing post-RTX IgG hypogammaglobulinemia (including our patients and other in the literature with available follow-up)[5,6], no life-threatening infections were detected. Among non-life-threatening infections, one patient presented bronchitis[6], one enteritis[6], and one recurrent episodes of acute otitis media. Moreover, evaluating the need of substitutive IgG infusion, 4 out of the 27 patients underwent IgG supplementation.…”
Section: Discussionmentioning
confidence: 86%
“…Delbe-Bertin et al[5] reported that persisting post-RTX IgG hypo-gammaglobulinemia was observed in 7 patients with IgG hypogammaglobulinemia before RTX infusion, while none of the 4 patients with normal pre-RTX IgG levels presented IgG hypogammaglobulinemia after RTX initiation. In addition, Fujinaga et al[6] found that nine out of 60 patients with complicated steroid-dependent NS showed hypogammaglobulinemia (defined as IgG levels < 500 mg/dL) after RTX infusion. Among these 9 patients, only 3 patients had normal IgG levels before the RTX infusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rituximab is generally safe and well tolerated in most children, there are potentially serious adverse events that require caution: hypogammaglobulinemia, late-onset neutropenia, hepatitis B reactivation, serious infusion-related adverse events and infections, the latter with potentially fatal outcome with reports of Pneumocystis jirovecii pneumonia and progressive multifocal leukoencephalopathy [8, 58,59,61,62,117,118] hematologic adverse effects are reported more often and more severely in younger children. In previous studies with SRNS [41] as well as with SDNS [119], those patients who developed severe neutropenia and hypogammaglobulinemia were aged under 10 years. In addition, in a Japanese multicentre study involving 114 children, the median age was significantly younger in patients with more severe hematologic adverse effects (6.4 vs. 11.5 years) [120].…”
Section: Anti-cd20 Monoclonal Antibodiesmentioning
confidence: 99%